2017
DOI: 10.7717/peerj.3641
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology controls recruitment of two invasive cyprinids: bigheaded carp reproduction in a navigable large river

Abstract: In the Mississippi River Basin of North America, invasive bigheaded carp (silver carp Hypophthalmichthys molitrix and bighead carp H. nobilis, also referred to as Asian carp) have spread rapidly over the past several decades. In the Illinois River, an important tributary of the Upper Mississippi River, reproduction appears to be sporadic and frequently unsuccessful, yet bigheaded carp densities in this river are among the highest recorded on the continent. Understanding the causative factors behind erratic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 23 publications
1
25
1
Order By: Relevance
“…For example, during 2009, a strong year-class of Silver Carp identified herein and during other studies within the Illinois River (Morgeson 2015;Stuck et al 2015) coincided with high river discharges. However, large yearclasses of Silver Carp in the middle Illinois River were also reported in 2008 (Gibson-Reinemer et al 2017) but not observed in this study, suggesting either that Silver Carp are not recruited into the adult population as age-0 fish or that mortality via commercial fishery harvest is effective at removing larger, older individuals from the population (i.e., Garvey et al 2012), precluding their capture throughout this study. Thus, although increases in discharge can promote stronger year-classes, Silver Carp recruitment can be successful under a wide range of environmental conditions.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations
“…For example, during 2009, a strong year-class of Silver Carp identified herein and during other studies within the Illinois River (Morgeson 2015;Stuck et al 2015) coincided with high river discharges. However, large yearclasses of Silver Carp in the middle Illinois River were also reported in 2008 (Gibson-Reinemer et al 2017) but not observed in this study, suggesting either that Silver Carp are not recruited into the adult population as age-0 fish or that mortality via commercial fishery harvest is effective at removing larger, older individuals from the population (i.e., Garvey et al 2012), precluding their capture throughout this study. Thus, although increases in discharge can promote stronger year-classes, Silver Carp recruitment can be successful under a wide range of environmental conditions.…”
Section: Discussioncontrasting
confidence: 48%
“…However, large year‐classes of Silver Carp in the middle Illinois River were also reported in 2008 (Gibson‐Reinemer et al. ) but not observed in this study, suggesting either that Silver Carp are not recruited into the adult population as age‐0 fish or that mortality via commercial fishery harvest is effective at removing larger, older individuals from the population (i.e., Garvey et al. ), precluding their capture throughout this study.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Additionally, a water level rise would increase the possibilities of larvae reaching productive floodplain habitats, including backwater lakes. On the La Grange Reach of the Illinois River, population dynamics of bighead carp Hypothalmichthys nobilis (Li et al 2009) and silver carp appear to be driven by sporadic spawning and recruitment linked to flooding (Gibson-Reinemer et al 2017).…”
mentioning
confidence: 99%